Electrochemistry of metal complexes and their use in amperometric sensors - Somasundrum, Mithran (Cranfield University, 1994)
This thesis concerns the utilization of metal complexes in amperometric sensors. Chapter One provides a general introduction to the area. The electrochemical theories relating to the development and use of amperometric sensors, are described, and applications for such sensors are outlined. These include trace element analysis for environmental and clinical use and the determination of NADH for the detection of clinical analytes. In Chapter Two, the electrochemical changes occurring in a ligand upon complexation, are examined as a possible method of selective metal ion detection. Screen-printing is used to produce disposable, single-use electrodes modified with the ligand bis- cyclohexanone oxaldihydrazone. At +250 mV vs SCE, the electrodes give a linear response to copper(II) across the range 30-300 pM (r = 0.983, n= 13). The effect on the electrode response of variations in pH, temperature, ligand content and storage time are outlined; as well as the effect of competing cations. In Chapter Three, pre-formed metal complexes are used as electron-transfer mediators. Part I considers homogeneous mediation from the enzyme NADH oxidase, using the Ru(lII/IV) redox couple. A scheme for enzyme amplification of the NADH response is outlined using alcohol dehydrogenase (ADH) and NADH oxidase. Additionally, ethanol determination is performed using an ADH/NADH oxidase bilayer. In Part 11, mediator immobilisation is examined using a novel ion-exchange/hydrogel composite (Nf/PVA). The structure of the composite is investigated by following the diffusional characteristics of both hydrophobic and hydrophilic mediators, incorporated within the film. An analytical application of the Nf(PVA layer is illustrated following the co-immobilisation of a mediator with glucose oxidase. The effect of protein adsorption onto the composite is also examined. Part HI of Chapter Three considers a possible alternative to mediated electrocatalysis, by using an electro- deposited film of poly(indole-5-carboxylic acid) (PICA). The overpotential. for the oxidation of ascorbate and NADH is lowered, apparently without the action of a redox mediating species. Strategies for the development of a PICA-based biosensor are outlined. Chapter Four provides an overview and general discussion of the experimental results and suggests areas for further work. These include further improvements to the design of the screen-printed electrodes in Chapter 2; the preferable choice of mediator for the immobilisation matrix in Chapter 3 Part 11, as well as possible methods of improving the biocompatability of the matrix; and a possible route to the immobilisation of NAD,, for the PICA-based system described in Chapter 3 Part III.